Observations on the biology of Afrotropical Hesperiidae (Lepidoptera). Part 9. Hesperiinae incertae sedis: Zingiberales feeders, genera of unknown biology and an overview of the Hesperiinae incertae sedis - Cock, Matthew J. W.; Congdon, T. Colin E.; Collins, Steve C. (Zootaxa, 2016)
The Afrotropical genera that have been recorded to feed on Zingiberales are documented. Partial life histories are presented for Erionota torus Evans (a South-East Asian species established in Mauritius), Semalea arela (Mabille), S. pulvina (Plötz), Xanthodisca vibius (Hewitson), X. rega (Mabille), Hypoleucis ophiusa (Hewitson), Caenides dacena (Hewitson), Osmodes adon (Mabille), Gretna cylinda (Hewitson) and Moltena fiara (Butler). Additional notes from the literature are provided on the genera Leona and Rhabdomantis. Notes on natural enemies of E. torus and M. fiara are included. We find that the Zingiberaceae and Costaceae feeding genera, Semalea, Xanthodiscus, Hypoleucis and Caenides (part) are united by a C-shaped raised rim to the prothoracic spiracle of the pupa. The pupa of Osmodes adon indicates this genus may have no close affinities to other Afrotropical genera for which the life history is known. The pupa of G. cylinda is unlike any other that we have documented and may reflect that this is the only species which we have found to be formed on the open leaf under surface rather than in a shelter. The early stages of M. fiara indicate affinities with Zophopetes and related genera. The paper concludes with a brief comparative discussion of the early stages of the Afrotropical Hesperiinae incertae sedis as a whole. There appear to be useful characters to group species by the ova and pupae but less so by the caterpillars. Based on pupae alone, the Hesperiinae incertae sedis might be divided into nine groups.